Fabrication and characterization of ferrimagnetic bioactive glass-ceramic containing BaFe12O19 - Wilaiwan Leenakul (2018)
Bioactivity of ferrimagnetic glass-ceramics is useful as thermo seeds for hyperthermia treatment of cancer. Ferrimagnetic glass-ceramics were prepared from the BaFe 12 O 19 (BF)-SiO 2 -CaO-Na 2 O-P 2 O 5 system using the incorporation method. The mixture was then further sintered at 800 °C to form the glass-ceramic samples. The structure and microstructure of the samples were characterized by X-ray diffraction, energy dispersive X-ray analysis (EDXA) and scanning electron microscopy. Magnetic hysteresis loops of the glass-ceramic samples were obtained with maximum field of 10 kOe, in order to evaluate the potential of these samples for hyperthermia treatment of cancer. In vitro bioactivity was investigated in simulated body fluid (SBF) for 14 days. The results showed that Na 2 Ca 2 Si 3 O 9 and BaFe 12 O 19 were the main phases in the glass-ceramic samples. Apatite was formed on the surface layers of the glass-ceramics, confirming their biocompatibility. It was found that the bioactivity increased with an increase in BF contents. © 2012 Elsevier Ltd and Techna Group S.r.l.